Konsep Al-Kaṣb Dalam Al-Qur’an (Studi Tafsir Mafātīḥ al-Ġayb Karya Fakhr al-Dīn al-Rāzī) - Intan Sari, Desi; Malik Ghozali, Abdul; Masruchin, Masruchin (Pascasarjana Institut Ilmu Al Quran (IIQ) Jakarta, 2023)
The purpose of this study is to find out the differences in kaṣb thought or other views of Fakhr al-Dīn al-Rāzī with Ash'ari. This study departs from the problem of whether there is a relationship between God's will and human actions according to Fakhruddin Al-Rāzī and whether Al-Rāzī's view of kaṣb is the same as that of Ash'ari. This research is a library-based research that starts from understanding interpretations related to human actions, in this case human actions are analyzed in the book of tafsir Mafatih Al-Ghaib. The findings of the study concluded that Al-Rāzī's idea or view of human actions (kaṣb) was that Al-Rāzī neither accepted nor completely rejected the theory of Ash'ari kaṣb which he called